2014
DOI: 10.1111/nan.12061
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal exposure to uranium results in direct transfer to the brain along olfactory nerve bundles

Abstract: These results suggest the existence of a transcellular passage from the mucosa to the perineural space around axon bundles. Uranium bypasses the blood brain barrier and is conveyed to the brain via the cerebrospinal fluid along the olfactory nerve. Future studies might need to integrate this new contamination route to assess uranium neurotoxicity after nasal exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Instillation avoids deposition in the lungs and/or on the fur which can occur with nose-only or whole-body inhalation exposure. Instillation has been used in several other studies to demonstrate the translocation of soluble or particulate materials in rodents (Evans and Hastings, 1992;Gianutsos et al, 1997;Henriksson et al, 1997;Ibanez et al, 2014;Tjälve et al, 1996). A lack of sensitivity of the animal model used in the present study (intranasal instillations in the rat) to explain the negative results obtained with alumina, is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…Instillation avoids deposition in the lungs and/or on the fur which can occur with nose-only or whole-body inhalation exposure. Instillation has been used in several other studies to demonstrate the translocation of soluble or particulate materials in rodents (Evans and Hastings, 1992;Gianutsos et al, 1997;Henriksson et al, 1997;Ibanez et al, 2014;Tjälve et al, 1996). A lack of sensitivity of the animal model used in the present study (intranasal instillations in the rat) to explain the negative results obtained with alumina, is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the neuronal pathway, nanoparticles could gain access to the CNS through the extracellular pathways (perineuronal, perivascular and cerebrospinal fluid pathways). As an example, to comfort initial inhalation studies using uranium aerosol (Tournier et al, 2009) in rats, that suggested the existence of an olfactory transport, a second wave of experiments using instillation of soluble uranium in the nasal cavity was performed (Ibanez et al, 2014).…”
Section: Extracellular Pathways Excluding Bloodmentioning
confidence: 99%
“…Mechanisms for adaptation to humans seem to have occurred in the BP precursor, B. pseudopertussis , at an earlier time, taking place for BP by gene loss (Diavatopoulos et al, 2005 ). B. pertussis infection damages nasal ciliated epithelium, a structure which transfers uranium to brain along olfactory nerve bundles (Wilson et al, 1991 ; Ibáñez et al, 2014 ).…”
Section: Data Supporting Amyloid-related Etiology According To Specifmentioning
confidence: 99%